¿Sé yo quién soy?: búsqueda de la identidad y duplicación especular en la tradición cervantina alemana temprana - Alfredo Moro Martín (E-Spania)
Don Quixote's encounters with the Knight of Mirrors and with the Knight of the White Moon mark two milestones in the chivalric career of Alonso Quijano. The self-confident knight, secure of his potential identity ends up giving way to the sober hidalgo who renounces knight-errantry to declare himself an enemy of all the knights belonging to Amadís de Gaula's lineage. The transition between these two versions of Alonso Quijano articulates, as Félix Martínez Bonati points out (116), a syntagmatic structure that implies a process of self-knowledge by the Spanish hidalgo and recognition of the surrounding reality. This syntagmatic structure is punctuated by a series of encounters with other gentlemen that represent «a labyrinth of mirrors», in the words of Roca Mussons (129-130), a series of mirrors that reflect, although obliquely, some traits of the protagonist himself. Through the use of the specular confrontation with these quixotic doubles, Cervantes’ novel articulates a sapiential journey that goes from the arrogant Quixote, the defeater of the Knight of the Mirrors, to the crepuscular Quixote defeated by the Knight of the White Moon. The aim of this work is to analyse these mirror reflections that Don Quixote encounters on his path towards chivalric renunciation in order to subsequently study how the first explicitly quixotic novel in German literature, Der teutsche Don Quichotte (1753) by W.E. Neugebauer makes use of this Cervantine resource of specular reduplication to articulate one of the most relevant themes of 18th century German narrative: the search for the identity of a young, inexperienced and idealistic protagonist.